Display of whole proteins on inner and outer surfaces of grapevine fanleaf virus‐like particles. Issue 12 (29th July 2016) - Belval, Lorène; Hemmer, Caroline; Sauter, Claude; Reinbold, Catherine; Fauny, Jean‐Daniel; Berthold, François; Ackerer, Léa; Schmitt‐Keichinger, Corinne; Lemaire, Olivier; Demangeat, Gérard; Ritzenthaler, Christophe
Summary: Virus‐like particles (VLPs) derived from nonenveloped viruses result from the self‐assembly of capsid proteins (CPs). They generally show similar structural features to viral particles but are noninfectious and their inner cavity and outer surface can potentially be adapted to serve as nanocarriers of great biotechnological interest. While a VLP outer surface is generally amenable to chemical or genetic modifications, encaging a cargo within particles can be more complex and is often limited to small molecules or peptides. Examples where both inner cavity and outer surface have been used to simultaneously encapsulate and expose entire proteins remain scarce. Here, we describe the production of spherical VLPs exposing fluorescent proteins at either their outer surface or inner cavity as a result of the self‐assembly of a single genetically modified viral structural protein, the CP of grapevine fanleaf virus (GFLV). We found that the N‐ and C‐terminal ends of the GFLV CP allow the genetic fusion of proteins as large as 27 kDa and the plant‐based production of nucleic acid‐free VLPs. Remarkably, expression of N‐ or C‐terminal CP fusions resulted in the production of VLPs with recombinant proteins exposed to either the inner cavity or the outer surface, respectively, while coexpression of both fusion proteins led to the formation hybrid VLP, although rather inefficiently. Such properties are rather unique for a single viral structural protein and open new potential avenues for the design of safe and versatile nanocarriers, particularly for the targeted delivery of bioactive molecules.